2010
DOI: 10.2175/106143010x12609736967080
|View full text |Cite
|
Sign up to set email alerts
|

Pilot‐scale Experience with Biological Nutrient Removal and Biomass Yield Reduction in a Liquid‐solid Circulating Fluidized Bed Bioreactor

Abstract: A pilot-scale liquid-solid circulating fluidized bed (LSCFB) bioreactor was developed at the Adelaide Pollution Control Plant, London, Ontario, Canada, to study its commercial viability for biological nutrient removal. Lava rock particles of 600 mm were used as a biomass carrier media. The LSCFB removed approximately 90% organic, 80% nitrogen, and 70% phosphorus at loading rates of 4.12 kg COD/m 3 ?d, 0.26 kg N/m 3 ?d, and 0.052 kg P/m 3 ?d, and an empty bed contact time of 1.5 hours. Effluent characterized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The actively growing microbial biomass usually requires management, which is typically accomplished by siphoning the thickest and oldest biofilm-coated particles that migrate to the top portion of the bed. Smaller sand sizes (effective size of 0.13-0.25 mm) allow the attachment of more biofilm, but require increased management to prevent the sand bed from overflowing at the biofilter outlet [62].…”
Section: Fluidized Bed Bioreactors (Fbbr)mentioning
confidence: 99%
“…The actively growing microbial biomass usually requires management, which is typically accomplished by siphoning the thickest and oldest biofilm-coated particles that migrate to the top portion of the bed. Smaller sand sizes (effective size of 0.13-0.25 mm) allow the attachment of more biofilm, but require increased management to prevent the sand bed from overflowing at the biofilter outlet [62].…”
Section: Fluidized Bed Bioreactors (Fbbr)mentioning
confidence: 99%
“…The experimental data obtained from the pilot-scale CFBBR 17 are used to calibrate the CFBBR model. Before that, these data must be preprocessed using the influent specifier in BioWin, and influent fractions are obtained that are associated with carbonaceous and nutrient fractions according to the biodegradable and nonbiodegradable organic matter in the influent wastewater.…”
Section: Methodsmentioning
confidence: 99%
“…In the pilot-scale CFBBR, the designed TCOD inf is 350 mg/L, and the designed TN inf is 40 mg/L. The amplitudes of the disturbances, ±40 mg/L in the TCOD inf concentration and ±10 mg/L in the TN inf concentration, 17 are taken into account, and then the estimated regions of TCOD inf and TN inf are 350 ± 40 mg/L TCOD inf and 40 ± 10 mg/L TN inf . In the TN inf −TCOD inf plane, the estimated region is represented as a rectangular zone.…”
Section: Methodsmentioning
confidence: 99%
“…The results from a pilot scale liquid-solid circulating fluidized bed (LSCFB) using lava rock media showed that approximately 90% organic, 80% N, and 70% phosphorus removals were achieved at loading rates of 4.12 kg COD/m 3 ·d, 0.26 kg N/ m 3 ·d, and 0.052 kg P/ m 3 ·d, respectively without the use of chemicals (Chowdhury, Nakhla, Zhu, and Islam, 2010). In a another experiment, the LSCFB was able to respond favourably to dynamic loadings by simulating a wet weather condition using a peaking factor of 3 for 4 hours .…”
Section: Biofilm Reactorsmentioning
confidence: 99%